The Effects of Service Quality on Customer Trust and Satisfaction in Internet Banking - Torres-Moraga, Eduardo; Barra, Cristóbal; Vásquez-Parraga, Arturo Z.; Farías, Antonio (Estudios de Administración, 2013)
Purpose - This study contributes a multidimensional measure of service quality impacting on the trust and satisfaction of customers using internet banking. Design/methodology/approach - Unlike previous studies reporting on independent factors of service quality affecting customer trust and satisfaction, this study elaborates and tests a multidimensional measure of service quality in the context of internet banking services. In addition, this study tests a proposed model and rival models showing how service quality impacts on customer trust and satisfaction.Findings - Service quality is a second-order factor with 6 dimensions revealing 6 important characteristics of the service quality that is expected in Internet banking. They are not separatecharacteristics of service quality but dimensions of a construct. The proposed model showing a direct impact of service quality on satisfaction and an indirect one on trust is the best tested model using structural equations. Research limitations/practical implications: The research limitations and practical implications of the results are discussed. Originality/value - The study elaborates and tests a multidimensional measure that is a comprehensive, and at the same time, parsimonious, approach to service quality when explainingcustomer trust and satisfaction in internet banking services